The Personal Creed Project: Portal to Deepened Learning - John Creger (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
The founder of an influential and transformative writing project reflects on its grounding in Moffett’s philosophy and presents the model of learning that grew out of it.